PREVALENCE OF VITAMIN A DEFICIENCY IN FISHERFOLK CHILDREN (6-8 YEARS) OF EAST GODAVARI DISTRICT AND EFFECT OF SUPPLEMENTATION OF ORANGE FLESHED SWEET POTATO - Y. RAJYA LAKSHMI DEVI *; S. THILAKAVATHY (The Journal of Research ANGRAU, 2021)
In today’s world, poverty still exists among people from lower strata and isolated communities. In India, 60.7% of the fisherfolk community are below the poverty line (BPL) and 97.3% of the fisherfolk of Andhra Pradesh are under BPL. One thousand artisanal fisherfolk children (6-8 years) from coastal regions of Kakinada were screened clinically for symptoms of Vitamin A deficiency and other micronutrient deficiencies. Among them, 23.4% showed moderate to severe clinical symptoms of Vitamin A deficiency and were selected for the study. The biochemical test results showed that the mean serum retinol of all the subjects was significantly below the standard values (0.2-0.5 mg/L). In the study, 100 gm of boiled orange fleshed sweet potato which provides 788μg of Retinol Activity Equivalents (RAE), thus, meeting 124.7% of the Recommended Dose of Allowance (RDA) was fed to the children 5 days a week for a period of six months. Orange fleshed sweet potato is a rich source of beta carotene and fibre. The subjects showed significant improvement in their clinical symptoms and 67% showed rise in their serum retinol levels after supplementation.